The Effectiveness of Health Education to The Womens Attitude in Facing Pre-Menopause - Laily Prima Monica (Journal of Ners and Midwifery, 2018)
Pre-menopause period is a natural thing for women and cannot be ignored or avoid but some women still havent learned about it, including changes in Physiology as well as psychic will happen after menopause. This research aimed to know the influence of health education on womans attitude towards time of pre-menopause. The research method used pre- experiments with design pre-test and post-test one group design. The sample in this research was 31 mothers aged 40-50 years in Polindes desa Pasirharjo kecamatan Talun kabupaten Blitar, which was determined by sampling total sampling technique. Treat- ment in the form of the granting of health education by lecturing methods lectures. The measurement of the attitude was done before and after the treatment. The instrument used a questionnaire. The data analysis technique used paired sample t-test. The mean value of the results of the study showed the average pre-test of the attitude of average value and 22,8 and flat post-test attitude 24,1. The data analysis showed the value of attitude p score value where p was 0.000 where p 0.046 so Ho was declined. The conclusion of the research was there was an effect of health and education towards womens attitudes about the pre-menopause in Polindes Desa Pasirharjo Kecamatan Talun Kabupaten Blitar. Based on the results of such research, it is suggested to women who experienced a period of pre menopause, can accept changes to physical and sexual abuse that happened to him at that time with the thought that menopause is a reasonable and positive holds events.